Development of the Evidence-Informed “OI Splint Kit” for Children with Osteogenesis Imperfecta and Their Families - Addab, Sofia; Thierry, Stephanie; Lafrance, Marie-Elaine; Jeong, Sunny; Brown, Jennifer; Brown, Carter; Plourde, Sylvie-Anne; Gugliotti, Angela; Thorstad, Kelly; Hamdy, Reggie; Rauch, Frank; Tsimicalis, Argerie (McGill journal of medicine, 2022)
Background: Children with osteogenesis imperfecta (OI) live in fear of fracturing a bone. As fractures are unpredictable, there is a need for tools and knowledge to immobilize a fracture during emergencies. Inspired by a patient recognized in their local OI community for fracture management, the aim of this patient-initiated project was to establish best practices for the safe handling of fractures, including the creation of an evidence-informed OI Splint Kit. Methods: A systematic review of the literature was conducted to identify kits and tools used to immobilize fractures during emergencies. An expert Task Force consisting of patients, clinicians, and decision makers was conjured to review the synthesized results. Priorities were delineated and a timeline was established to create the OI Splint Kit. The prototype underwent iterative cycles of modifications based on feedback from the Task Force. Results: Four electronic data bases were searched (Medline, CINHAL, PsychInfo, and Scopus), revealing zero publications pertaining to kits for fracture immobilization. The Task Force used their clinical expertise and patient experiences to develop the OI Splint Kit. The following items were included: splinting tools, bilingual educational material, instructional cards, video tutorials, and a memory card game. Conclusion: A gap remains in validated kits to assist in fracture immobilization during emergencies. A tangible and practical OI Splint Kit was developed to fulfill this need, based on inter-professional clinical expertise and patient experiential knowledge. The kit is subject to rigorous testing and ongoing quality evaluations, ensuring it will be suitable for use in various contexts.